2018
DOI: 10.3390/molecules23071604
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Candidate Genes Related to Aroma Formation in Osmanthus fragrans

Abstract: Osmanthus fragrans, or “RiXiangGui”, is an ornamental, woody, evergreen plant that is cultivated widely because it blooms recurrently and emits a strong fragrance. Recently, the germplasm resources, classification, and aroma compositions of O. fragrans have been investigated. However, the molecular mechanisms of the floral scent formation and regulation have remained largely unknown. To obtain a global perspective on the molecular mechanism of the aroma formation during blooming, nine RNA Sequencing (RNA-Seq) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Recently, a set of genetic markers was identified 14 , 15 , and an effort to construct a genetic linkage map was reported 16 . Additionally, several transcriptomics studies identified a large number of genes that are differentially expressed in some of the cultivars with attractive traits 17 , 18 . While these studies indirectly associate the diverse phenotypes with the genotypes of sweet osmanthus, there is no genome information that can directly link the specific genes to particular traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a set of genetic markers was identified 14 , 15 , and an effort to construct a genetic linkage map was reported 16 . Additionally, several transcriptomics studies identified a large number of genes that are differentially expressed in some of the cultivars with attractive traits 17 , 18 . While these studies indirectly associate the diverse phenotypes with the genotypes of sweet osmanthus, there is no genome information that can directly link the specific genes to particular traits.…”
Section: Discussionmentioning
confidence: 99%
“…fragrans has been examined through aroma compounds 4 6 , essential oils 7 10 , and taxonomy using various molecular markers 11 – 16 . Transcriptome studies have determined the genes that might be responsible for the emission of flower scent in O. fragrans 17 , 18 . Gene expression has also been modulated at different flowering stages of O .…”
Section: Introductionmentioning
confidence: 99%
“…It is usually served as an additive in food, tea and other beverages [ 17 , 18 ], and the flower oil of O. fragrans has a mildly sedative effect on controlling the energy balance of the body in terms of the prevention of over-eating and gaining weight [ 18 20 ]. Though many studies about O. fragrans development and application have been reported in the recent years [ 18 , 19 , 21 26 ], there is no study reported to address the genome-wide identification of the microRNAs in O. fragrans, which impeded the comprehensive understanding of the regulation networks during O. fragrans development. Therefore, entirely identifying the miRNAs and analyzing their functions in O. fragrans can further provide important additional information about the regulatory mechanisms in the biological processes of O. fragrans and will be useful to isolate high-quality and native medical or economical products from O. fragrans .…”
Section: Introductionmentioning
confidence: 99%
“…OfRPB2 was used as internal normalization for different flowering stages [31]. The qRT-PCR data were determined with the method described in Yang et al [32].…”
Section: Rna Extraction and Qrt-pcr Analysismentioning
confidence: 99%